Peptide Mimotopes of Complex Carbohydrates in Salmonella enterica Serovar Typhi Which React with Both Carbohydrate‐Specific Monoclonal Antibody and Polyclonal Sera from Typhoid Patients - Thong, Kwai Lin; Tang, Swee Seong; Tan, Wen Siang; Devi, Shamala (Wiley, 2007)
Polyclonal sera from typhoid patients and a monoclonal antibody, mAb ATVi, which recognizes the capsular polysaccharide Vi antigen (ViCPS), were used to select for peptides that mimic the ViCPS by using a phage‐displayed random 12‐mer peptide library. Two major common mimotopes selected from the library carried the amino acid sequences TSHHDSHGLHRV and ENHSPVNIAHKL. Enzyme‐linked immunosorbent assays (ELISAs) showed that these peptides carry mimotopes to ViCPS. Phage clones that contained the 12‐mer peptides were also tested against pooled/individual typhoid patients' sera and found to have 3 to 5 times higher binding compared to normal sera. By using Phage‐ELISA assays, the derived synthetic peptides, TSHHDSHGLHRV and ENHSPVNIAHKL, were tested against a monoclonal antibody mAb ATVi and over 2‐fold difference in binding was found between these peptides and a control unrelated peptide, CTLTTKLYC. Inhibition of the mAb's binding to ViCPS indicated that the synthetic peptides successfully competed with the capsular polysaccharide for antibody binding.